Preclinical study the pharmacokinetics new anxiolytic drug of dipeptide structure GB-115 - V. P. Zherdev; S. S. Boyko; E. V. Blynskaya; K. G. Turchinskaya; T. A. Gudasheva; E. V. Ivannikova (Фармакокинетика и Фармакодинамика)
The paper presents the results of experimental studies of pharmacokinetics GB-115 after oral administration of crystalline and micronized substances and 4 new laboratory samples pharmaceutical compositions which differ in the technology of preparation and composition of excipients. It is shown that different excipients and preparation technology significantly affect the pharmacokinetics and effect of studied dipeptide; its optimization is improve the pharmacokinetics properties of the developed compound, namely increasing completeness of absorption, maximum concentration, rate and extent of absorption in the final result in bioavailability GB-115. On the basis of experimental data obtained two pharmaceutical compositions recommended for further pharmacological study.